Synthesis and photophysical properties of pyrene-labeled 3-deaza-2′-deoxyadenosines comprising a non-π-conjugated linker: fluorescence quenching-based oligodeoxynucleotide probes for thymine identification. Issue 42 (4th September 2015) - Aso, Tatsuya; Saito, Koichiro; Suzuki, Azusa; Saito, Yoshio
Abstract : ODN probes containing py3z A (1 ) exhibited remarkable fluorescence quenching only when the opposite base of the complementary strand was thymine. Abstract : Pyrene-labeled 3-deaza-2′-deoxyadenosine comprising a non-π-conjugated linker py3z A (1 ) was synthesized and its photophysical properties were investigated. Oligodeoxynucleotide (ODN) probes containing py3z A (1 ) exhibited remarkable fluorescence quenching only when the opposite base of the complementary strand was the perfectly matched thymine. Such fluorescence quenching-based ODN probes exhibited excellent on-off switching properties, making them useful tools for single nucleotide polymorphism (SNP) genotyping and for the identification of target genes and structural studies of nucleic acids.